The Effect of Workload, Work Motivation, and Teamwork on Employee Performance - Asep Saepuloh; Tetty Sufianty Zafar; Dicky Jhoansyah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the influence of workload, work motivation, and teamwork on employee performance at Moen's Farm in Cidahu, Sukabumi Regency. This study uses a quantitative method with a survey approach by distributing questionnaires to the entire population of 110 employees, with a saturated sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS 27 software. The results of the study indicate that the three independent variables, namely workload, work motivation, and teamwork, simultaneously and partially have a significant effect on employee performance. The coefficient of determination of 60.5% indicates that the combination of the three variables is able to explain employee performance, while the rest is influenced by other factors not examined. Workload has a positive influence on performance, which means that the more balanced the workload, the better the performance. High work motivation also improves performance, as does effective teamwork. These findings are expected to provide input for Moen's Farm management in improving employee performance through workload management, providing appropriate motivation, and forming a solid work team.